Journalism - Vos, Tim P. (Handbooks of communication science ;, 2018)
This volume sets out the state-of-the-art in the discipline of journalism at a time in which the practice and profession of journalism is in serious flux. While journalism is still anchored to its history, change is infecting the field. The profession, and the scholars who study it, are reconceptualizing what journalism is in a time when journalists no longer monopolize the means for spreading the news. Here, journalism is explored as a social practice, as an institution, and as memory. The roles, epistemologies, and ethics of the field are evolving. With this in mind, the volume revisits classic theories of journalism, such as gatekeeping and agenda-setting, but also opens up new avenues of theorizing by broadening the scope of inquiry into an expanded journalism ecology, which now includes citizen journalism, documentaries, and lifestyle journalism, and by tapping the insights of other disciplines, such as geography, economics, and psychology. The volume is a go-to map of the field for students and scholars--highlighting emerging issues, enduring themes, revitalized theories, and fresh conceptualizations of journalism.